Primary Sarcomas of the Larynx: A Case Series of Four Different Histopathologic Types - Abu-Dayeh, Ala S.; Murshed, Khaled A.; Ammar, Adham; Petkar, Mahir (Avicenna Journal of Medicine, 2023)
Primary laryngeal sarcomas are rare. Their nomenclature and classification are similar to soft tissue counterparts; however, there are notable differences between clinical presentation, behavior, treatment, and follow-up. There is sparse information regarding the clinical features, biologic behavior, and treatment modalities of laryngeal sarcomas. To increase our understanding about these tumors, we describe herein an additional series of four cases of different pathologic types of laryngeal sarcomas, including low-grade chondrosarcoma, leiomyosarcoma, well-differentiated liposarcoma, and undifferentiated pleomorphic sarcoma. Our main aim is to upsurge awareness about the morphologic variations of laryngeal sarcomas, to avoid potential pitfalls during histopathologic examination. It is essential to ensure that correct diagnosis, subclassification, and grading are achieved for proper guidance of treatment and clinical follow-up at multidisciplinary team meetings.
Keywords: larynx; sarcoma; chondrosarcoma; leiomyosarcoma; liposarcoma; undifferentiated pleomorphic sarcoma